A concept paper: “the development of sky arms: a novel system for alleviating edema using the 4D development model” - Aung, Khin Thandar; Aung, Thurein; Abdul Razak, Rafiza (Global Academic Excellence (M) Sdn Bhd, 2024)
Millions of people worldwide suffer from oedema, a condition that frequently shows up as swelling in the upper extremities and is characterized by an abnormal buildup of fluid in tissues. Efficient management of oedema is crucial for alleviating symptoms and improving patient outcomes, typically achieved through elevating the limbs to aid in fluid drainage. However, current methods, such as traditional arm slings and bandages connected to IV stands, have significant drawbacks, including limited adaptability, discomfort, inadequate support, and environmental issues due to frequent bandage changes. This concept paper introduces Sky Arms, an innovative device designed to revolutionise the management of upper limb oedema. Sky Arms is a limb elevation device incorporating cutting-edge materials, digital technology, dynamic customisation, and data-driven feedback. It will be developed using the 4D Development Model to provide a user-friendly, secure, and adaptable experience. This study explores the features of SkyArms, the role of the 4D Model in enhancing therapy effectiveness, the potential impact on patient care and recovery, and the opportunities for collaboration in the social sciences, education, and innovation. Sky Arms offers a promising solution to the persistent problem of oedema through the implementation of the 4D Development Model. This study highlights its innovative methodology and potential benefits, advocating for interdisciplinary cooperation to bring this technology to fruition. Sky Arms represents a significant advancement in oedema treatment, offering the potential for improved patient outcomes, a higher quality of care, and reduced healthcare costs.